SMEs development and corruption: case of Kazakhstan - Suleimenova, Gulimzhan; Sadvokassova, Aigul; Rakisheva, Botagoz; Nurmaganbetov, Arman (Business: Theory and Practice, 2018)
The article presents a study of the corruption perception and the involvement of SMEs in corruption practices. The main goal of the paper is to provide an analysis of corruption perception of the SMEs representatives, its parts and research methodology to provide an adequate picture and analysis of corruption of the Kazakhstan. For obtaining a comparative picture, we interviewed 500 representatives of SMEs and 500 civil servants. We used a mass survey (face-to-face) method. The results show that the presence of “gap” between perception of corruption and degree of the respondents’ involvement in corrupt practices. The respondents believe that corruption is widespread, but they themselves were rarely involved in corrupt practices. The key message is that the SMEs representatives consider this problem to be acute, but they are not ready to talk about their own experience in this regard.